PENGARUH NAUNGAN TERHADAP KARAKTER MORFOLOGI DAUN SERTA HASIL DUA VARIETAS TANAMAN KEDELAI (Glycine max L. Merill) (Effect of Shading to Leaf Morphology Characters on Soybean Varieties (Glycine max L. Merill)) - Agung Budi Hariyadi; Nerty Soverda; Elly Indraswari (Bioplantae, 2012)
This research aims to study the effect of shade on leaf morphological characters and yield of two soybean varieties. The experiment was conducted at the Experimental Farm Faculty of Agriculture, University of Jambi. Materials and tools used are 1 unit paranet 50%, soybean seed varieties Petek (shade tolerant) and Variety Jayawijaya (shade sensitive), manure, NPK Pearl, Fungicides and Insecticides. Tools used include field equipment, calipers, Kutek nodes, solatip clear, glass objects, microscopes, analytical scales, tweezers, scissors, and pens. This experiment uses split plot design consisting of 2 factors. The first factor as the main plot is a shade (N), which consists of two levels, namely the auspices of 0% (no shade) and 50% shade. The second factor is the subplot is that soybean varieties, Petek and Jayawijaya. The results showed that the varieties Petek shows consistency as shade tolerant varieties with traits such shows lower leaf thickness, leaf area reduction in the lower and decreased stomatal density lower than the Jayawijaya (sensitive). Treatment shade and treatments varieties also significantly influenced variable leaf area, weight of 100 seeds, but there is no interaction between treatment shade varieties. Meanwhile, the variable thickness of the leaves, stomata density, number of pods per plant, and yield per plant only significantly different to shade treatments. In addition, Petek Variety show consistency with the provision of shade tolerance of 50% of the variable leaf thickness, leaf area and stomatal density compared Jayawijaya varieties (sensitive).Keywords: Soybean, shade, leaf morphological characters.